Development of semi-automatic solar gate system for electromechanical part - Mohd Hisyammudin, Muda (2008)
Development of semi-automatic solar gate system for electro-mechanical part is important to open and close the sliding gate. It is uses just a simple system and easy to overhaul this system. It is also safe for the children and to adult too. This system is divided into two groups such as mechanical part and electrical part. For mechanical part, it is designed to be a guard for electrical part. It is also designed to place a solar panel to convert sun light to be an electric current to recharge batteries. With this system, it can save the cost and safe to use. In general, this project is divided into two parts which are mechanical and electrical part.